The Czech Republic SimSmoke: The Effect of Tobacco Control Policies on Smoking Prevalence and Smoking Attributable Deaths in the Czech Republic. (21st February 2012) - Levy, David T.; Ross, Hana; Kmetova, Alexandra; Kralikova, Eva; Stoklosa, Michal; Blackman, Kenneth
Abstract : Background . The Czech Republic has a weak tobacco control record. This paper describes a simulation model examining the effect of future tobacco control policies in the Czech Republic on smoking prevalence and associated future premature mortality. Methods . The model is developed using the SimSmoke simulation model of tobacco control policy. The model uses population, smoking rates and tobacco control policy data for the Czech Republic. It assesses, individually and in combination, the effect of taxes, smoke-free air laws, mass media campaigns, advertising bans, warning labels, cessation treatment, and youth access policies. Results . With a comprehensive set of policies, smoking prevalence can be reduced by as much as 22% in the first year, by 35% in 20 years, and up to 40% in 30 years. By 2040, 5, 873 deaths can be averted in that year alone. Without these policies, 113, 004 people in the Czech Republic will die prematurely in the next 30 years. Conclusions . The model shows that significant inroads to reducing smoking prevalence and premature mortality can be achieved through tax increases, a high intensity media campaign, a comprehensive cessation treatment program, strong health warnings, stronger smoke-free air laws and marketing bans, and well-enforced youth access laws.